THE RELATIONSHIP BETWEEN TIKTOK VIEWING INTENSITY AND STUDENTS' LEARNING CONCENTRATION - Ria Rosalina; Sintia Ramadhani; Andrian Afandi (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
The development of social media, particularly TikTok, has become part of students' daily lives and has the potential to impact the learning process. This study aims to determine the relationship between TikTok viewing intensity and students' learning concentration. This study used a quantitative method with a correlational approach. Data were obtained from 51 respondents via questionnaire and analyzed using a Pearson correlation test using RStudio software. The analysis results showed a correlation coefficient of r = 0.121 with a significance value of p = 0.397 (p > 0.05). These results indicate that the relationship between TikTok viewing intensity and students' learning concentration is very weak and insignificant. Therefore, it can be concluded that TikTok viewing intensity does not have a significant relationship with students' learning concentration.